The retention of teachers - Clayton, Patricia Ann (Cranfield University, 1995)
In the late 1980s, in Britain, teacher retention was an important issue in public education, with inner city schools suffering most from teachers' unwillingness to be retained. Most labour market studies, even those written about teachers, concentrate on the 'demand side' : there are few empirical studies of the supply side. Those researched from the perspective of the employees themselves are rare. A literature search yielded three main categories of supply side job satisfactions : groupings of 0 intrinsic, extrinsic and contextual factors. A research approach was developed to establish the significance and stability of such factors in teaching. The method was one of refinement from qualitative exploration to quantitative explanation. The field work began with an analysis of student writings about their most valued experiences in informal educational settings, continued with interviews with four head teachers and tested the abstracted satisfaction characteristics with two populations : trainee teachers and established teachers. The retention factors identified were adequate resources, colleagues, community support and the feeling of doing a worthwhile job allowing for personal and professional development, in the 0 context of stable educational policy. Results were obtained by correlation and principal components analysis. A contrast is drawn between quit factors and stay factors. This analysis focuses on the collegiate nature of schools and teaching. Experienced tea6hers concur, extending this collegiality towards 00 relationships with the community through parents and governing bodies. Gender is found to be a b consistent correlate. The conclusion discusses retention and motivation in the light of the findings. Retention policies are found to omit the professional concerns of teachers. In effect, evidence of vocationalism challenges the dependence of retention on extrinsic as distinct from intrinsic and contextual factors. Gender seems to be systematically ignored by employers, particularly in attempts to proletarianise teaching, despite the statistical evidence that it is a ferninised occupation.